A MORTE COM DIGNIDADE E A AUTONOMIA DO INDIVÍDUO: uma discussão sobre a necessidade de regulamentação da ortotanásia no Brasil - OLIVEIRA, Diego Ferreira de (2016)
The research analyzes the subject of death with dignity and individual autonomy from the (non) performance of the Brazilian state in regulating and promoting the practice of orthothanasia. The delimitation of the problem of the present study considers that the autonomy of the individual is a constitutional principle imbricated with the principle of freedom and the principle of human dignity. Thus, the problem faced in the research is the treatment of this issue by the State when facing issues relating to regulation of orthothanasia, which is meant to adapt to the idea of death with dignity. The analysis discusses the dignified death and the right choices at the end of life, especially when the person is terminally ill or irreversible situation of great suffering. To this end, four specific objectives were established, each corresponding to a chapter of the research: a) to analyze the concept of autonomy of the individual facing death from theoretical frameworks of John Rawls, Ronald Dworkin and its correlation with the dignity of the person human in the event death round about; b) analyze the concepts of euthanasia, orthotanasia futility, mistanásia, palliative care, among others, as well as the legal subject of death with dignity in Brazil and Comparative Law; and c) evaluate the need for regulation and the implementation of orthothanasia and palliative care and responsibility of the Brazilian state to meet these desiderata. We conclude that there is an urgent need for objective and firm action by the Legislature and Executive, for the purpose of regulating and implementing the assured practice of orthothanasia and palliative care in health facilities in Brazil.